Novel cervical pedicle screw design to enhance the safety insertion without compromising biomechanical strength - Pilan Jaipanya; Pongsthorn Chanplakorn; Annop Sikongkaew; Anak Khantachawan; Suphaneewan Jaovisidha; Thamrong Lertudomphonwanit (PLoS ONE, 2025)
Background Lateral mass screw (LMS) is a more widely adopted method for posterior cervical spine fixation than the cervical pedicle screw (CPS). Despite its lower pullout strength, the insertions of LMS are more reproducible and have a lower risk. CPS insertion is a technically demanding procedure due to the small pedicle channel. Thus, CPS insertion has a high risk of pedicle wall perforation, resulting in neurovascular injury. For these reasons, surgeons may avoid CPS insertion despite its benefit of greater biomechanical strength. Therefore, an improvement in the CPS design is needed to avoid this catastrophic complication. Objectives To develop a new design of CPS, aiming to decrease pedicle wall perforation, while maintaining the biomechanical properties comparable to those of standard CPS. Materials & methods To reduce the risk of pedicle wall perforation, a novel CPS design should be configured in tapered shape, with a tapering screw pitch and thread diameter with a self-tapping thread. A bilayer bone finite element model representing the cortical and cancellous bone of the cervical spine pedicle was used for pullout strength test. According to our CT-based study of cervical pedicle anatomy in a normal population, the final CPS was created according to the parameters that yielded the best biomechanical strength according to finite element studies. The safety of CPS insertion, in terms of pedicle wall penetration, was assessed in 3D-printed cervical spine models of C3-C7. The pullout test was subsequently performed in a tri-layer sawbones foam model to compare the novel CPS, convention CPS, and lateral mass screw. Results The final screw design was a taper configuration with core diameter from 2.5 to 2.0 mm, thread diameter from 4.0 to 2.5 mm and pitch length from 1.0 to 1.25 mm. A total of 60 screws (30 conventional CPS screw and 30 Novel CPS screw) were tested in 6 3D cervical spine models. No case of pedicle wall perforation were found in the novel-design CPS group. In the conventional CPS group, 8 pedicle wall perforations were encountered, which was a statistically significant difference (p = 0.002). The novel CPS screw design and conventional CPS screw yielded pullout strengths of 449.7 N and 495.0 N, respectively, which showed no statistical difference. The LMS screw yielded a pullout strength of 168.3 N, showing statistically less strength compared with the 2 types of CPS screws. Conclusions The proposed novel CPS could decrease pedicle wall perforation and enhance the safety of screw insertion. Its pullout strength is comparable to that of a 3.5-mm standard CPS and superior to that of a 3.5-mm lateral mass screw.